2014
DOI: 10.1098/rspb.2014.0751
|View full text |Cite
|
Sign up to set email alerts
|

Moving in time: Bayesian causal inference explains movement coordination to auditory beats

Abstract: Many everyday skilled actions depend on moving in time with signals that are embedded in complex auditory streams (e.g. musical performance, dancing or simply holding a conversation). Such behaviour is apparently effortless; however, it is not known how humans combine auditory signals to support movement production and coordination. Here, we test how participants synchronize their movements when there are potentially conflicting auditory targets to guide their actions. Participants tapped their fingers in time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…Third, performance was better in 1-2-3-Go condition in which subjects made two measurements, as evidenced by a lower root-mean-square error (RMSE) in 1-2-3-Go compared to 1-2-Go condition ( Fig 2C; permutation test; p-value < 0.01 for all subjects). This observation indicates that subjects combined the two measurements to improve their estimates, corroborating reports from other behavioral paradigms [46][47][48][49][50][51][52][53][54]. Combined with the systematic bias toward the mean of t s , these results indicated that subjects integrated prior information with one or two measurements to improve their performance.…”
Section: Subjects Integrate Interval Measurements With Prior Knowledgesupporting
confidence: 85%
“…Third, performance was better in 1-2-3-Go condition in which subjects made two measurements, as evidenced by a lower root-mean-square error (RMSE) in 1-2-3-Go compared to 1-2-Go condition ( Fig 2C; permutation test; p-value < 0.01 for all subjects). This observation indicates that subjects combined the two measurements to improve their estimates, corroborating reports from other behavioral paradigms [46][47][48][49][50][51][52][53][54]. Combined with the systematic bias toward the mean of t s , these results indicated that subjects integrated prior information with one or two measurements to improve their performance.…”
Section: Subjects Integrate Interval Measurements With Prior Knowledgesupporting
confidence: 85%
“…The central PC claim that the brain uses Bayesian inference when choosing a plausible metrical model for a given rhythmical input was recently supported experimentally. Using a finger‐tapping paradigm, Elliot and colleagues provided evidence suggesting that humans exploit a Bayesian inference process to control movement timing when facing microtemporal differences . They presented two metronomes of equal tempo but differing in phase and temporal regularity to participants and asked participants to synchronize their tapping with the experienced beat.…”
Section: Predictive Coding Of Rhythmmentioning
confidence: 99%
“…Using a finger-tapping paradigm, Elliot and colleagues provided evidence suggesting that humans exploit a Bayesian inference process to control movement timing when facing microtemporal differences. 37 They presented two metronomes of equal tempo but differing in phase and temporal regularity to participants and asked participants to synchronize their tapping with the experienced beat. When participants chose to integrate the two timing cues into a single-event estimate, modeling the behavior as a Bayesian inference process provided a better description of the data than other plausible models.…”
Section: Predictive Coding Of Rhythmmentioning
confidence: 99%
“…Work by Bolt and Loehr has described a relationship not only between an individual's own performance stability and joint agency but also between reliability of a co-actor's actions and a shared sense of control (Bolt and Loehr, 2017). Previous work has suggested that assessing and attributing agency is dependent on the sensory reliability and distinctiveness of the signal (Elliott, M. T., Wing, A. M., & Welchman, 2014). This issue in particularly germane in choral singing, for example, where individuals adjust the intensity of their vocal output in order to optimize the so-called "self-to-other ratio", which reflects the degree to which an individual can hear their own sounds amongst co-performers' sounds (Ternström, 2003).…”
Section: Self-other Distinction and Self-other Blurringmentioning
confidence: 99%